2013
DOI: 10.1212/wnl.0b013e3182918ca6
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid imaging and CSF biomarkers in predicting cognitive impairment up to 7.5 years later

Abstract: Objectives: We compared the ability of molecular biomarkers for Alzheimer disease (AD), including amyloid imaging and CSF biomarkers (Ab 42 , tau, ptau 181 , tau/Ab 42 , ptau 181 /Ab 42 ), to predict time to incident cognitive impairment among cognitively normal adults aged 45 to 88 years and followed for up to 7.5 years.Methods: Longitudinal data from Knight Alzheimer's Disease Research Center participants (N 5 201) followed for a mean of 3.70 years (SD 5 1.46 years) were used. Participants with amyloid imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
174
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(191 citation statements)
references
References 39 publications
14
174
1
Order By: Relevance
“…Thus considered together, the results indicate that in otherwise healthy older adults, evidence of amyloidosis is associated with cognitive decline, mainly in memory, and this decline is increased substantially among 34 carriers. Table 2 Results of linear mixed model, mean slopes (SD), and magnitudes of difference (Cohen's d) Cohen (1988) and Newcombe (2006) The results of this study are not consistent with those from earlier prospective studies which reported that 34 carriage did not increase Ab-related cognitive decline in healthy older adults (Doraiswamy et al, 2012;Lim et al, 2012;Roe et al, 2013). As the samples of Abþ healthy older adults studied in these previous studies were smaller, or studied over shorter time intervals than in the present study and in Mormino et al (2014), the absence of any interaction between 34 and Ab observed in these previous studies is most likely to reflect insufficient statistical power to detect the effect of APOE 34 on Ab-related cognitive decline, especially given the subtlety of this effect (i.e., d ¼ 0.4 for visual memory).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Thus considered together, the results indicate that in otherwise healthy older adults, evidence of amyloidosis is associated with cognitive decline, mainly in memory, and this decline is increased substantially among 34 carriers. Table 2 Results of linear mixed model, mean slopes (SD), and magnitudes of difference (Cohen's d) Cohen (1988) and Newcombe (2006) The results of this study are not consistent with those from earlier prospective studies which reported that 34 carriage did not increase Ab-related cognitive decline in healthy older adults (Doraiswamy et al, 2012;Lim et al, 2012;Roe et al, 2013). As the samples of Abþ healthy older adults studied in these previous studies were smaller, or studied over shorter time intervals than in the present study and in Mormino et al (2014), the absence of any interaction between 34 and Ab observed in these previous studies is most likely to reflect insufficient statistical power to detect the effect of APOE 34 on Ab-related cognitive decline, especially given the subtlety of this effect (i.e., d ¼ 0.4 for visual memory).…”
Section: Discussioncontrasting
confidence: 73%
“…However, potential interactions between Ab and 34 carriage were suggested by observations in 2 different cohorts that associations between Ab levels and memory performance were evident only in 34 carriers (Kantarci et al, 2012;Lim et al, 2013aLim et al, , 2013bLim et al, , 2013c. Initial prospective studies in preclinical AD showed that rates of Ab-related memory decline were not increased when 34 carrier status was added to predictive models (Doraiswamy et al, 2012;Lim et al, 2012;Roe et al, 2013), suggesting that the risk for memory decline and AD posed by 34 carrier status was a consequence of 34 carriage accelerating Ab accumulation. However, a recent analysis of data aggregated from 3 different prospective studies of early AD observed that 34 carrier status increased substantially the rate of memory decline over a median of 1.5 years in Ab positive (Abþ) healthy individuals (Mormino et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These relationships also survived corrections for cortical volume and thickness and were independent of age and sex, suggesting that despite sharing a large proportion of variance with volume and thickness, there is a unique relationship between cognitive function and cortical gyrification in the lateral frontal cortex. Our results in this population are also relevant in the context of cognitive aging, as there are indications that the cognitive difficulties that are observed in older adulthood are related to brain [48] and cognitive health [49,50] much earlier in the lifespan. Given the age-related vulnerability of the frontal cortex to volume decrease and its important role in cognitive aging, it is of value to document if prefrontal gyrification relates to cognitive function, especially in a midlife population who are still underinvestigated in the literature.…”
Section: Discussionmentioning
confidence: 55%
“…AD is characterized histologically by an abundance of extracellular amyloid-b (Ab) plaques (see Glossary) in the brain as well as the widespread presence of hyperphosphorylated tau (microtubule-associated protein tau, MAPT) aggregates within neurons (neurofibrillary tangles) [1-3]. Accumulation of amyloid plaque in the brain takes place over many years and typically precedes tau tangles and cognitive decline by a decade or more [4][5][6][7].…”
Section: Trem2: Presenting Microglia Front and Center In Admentioning
confidence: 99%
“…AD is characterized histologically by an abundance of extracellular amyloid-b (Ab) plaques (see Glossary) in the brain as well as the widespread presence of hyperphosphorylated tau (microtubule-associated protein tau, MAPT) aggregates within neurons (neurofibrillary tangles) [1-3]. Accumulation of amyloid plaque in the brain takes place over many years and typically precedes tau tangles and cognitive decline by a decade or more [4][5][6][7].Another histological feature of AD is the presence and accumulation of reactive astrocytes and microglia (Box 1) around plaques [8,9], loosely called 'neuroinflammation' but more aptly classified as astrogliosis and microgliosis [10][11][12]. Microglia are a self-renewing population of myeloid cells that establish permanent brain residence during embryonic development and function as the innate immune cells of the brain throughout life [13].…”
mentioning
confidence: 99%